1989
DOI: 10.1103/physrevb.39.10791
|View full text |Cite
|
Sign up to set email alerts
|

Theory of hydrogen diffusion and reactions in crystalline silicon

Abstract: The behavior of hydrogen in crystalline silicon is examined with state-of-the-art theoretical techniques, based on the pseudopotential-density-functional method in a supercell geometry. Stable sites, migration paths, and barriers for different charge states are explored and displayed in totalenergy surfaces that provide immediate insight into these properties. The bond-center site is the global minimum for the neutral and positive charge states; in the negative charge state, the tetrahedral interstitial site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
257
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 548 publications
(291 citation statements)
references
References 63 publications
20
257
6
Order By: Relevance
“…This behavior of hydrogen was confirmed and described in great detail with a variety of experimental techniques [8][9][10][11]. In parallel, theory and computation [12][13][14][15] elucidated the physics of hydrogen's interactions with semiconductors, and established the correlation between its atomic and electronic structure. In a compound semiconductor, H + wants to reside in the vicinity of the anion, which can be explained based on Coulomb attraction between the proton and the electronic charge density around the more electronegative anion.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This behavior of hydrogen was confirmed and described in great detail with a variety of experimental techniques [8][9][10][11]. In parallel, theory and computation [12][13][14][15] elucidated the physics of hydrogen's interactions with semiconductors, and established the correlation between its atomic and electronic structure. In a compound semiconductor, H + wants to reside in the vicinity of the anion, which can be explained based on Coulomb attraction between the proton and the electronic charge density around the more electronegative anion.…”
Section: Introductionmentioning
confidence: 87%
“…We obtain the formation energy of interstitial hydrogen in charge state q (where q= −1, 0, or +1) by placing the hydrogen impurity in a volume of host material, calculating the total energy E tot (H q ) of this structure, and subtracting the energy E tot (bulk) of a corresponding volume of pure host material [15,16]:…”
Section: Methodsmentioning
confidence: 99%
“…The calculation were based on the Si-Si bond length change caused by the incorporation of an H atom to the bond-centered site, predicted by theory to be 0.83 Angstrom. [31] The calculation were facilitated by TRIM [75] derived damage and hydrogen distributions, which were modified to provide depth scales compatible with the data presented in figure 5-4 The result of the strain calculations as a function of hydrogen occupation of the bondcentered sites is presented in figure 5-18. As can be seen, the depth of maximum out-ofplane tensile strain increases with increasing amount of H residing at the bond-centered site, as expected considering the increasing influence of H to the total out-of-plane tensile strain.…”
Section: Influence Of Stress and Strain Field On H-platelet Formationmentioning
confidence: 99%
“…Theory predicts a change from the Si-Si bond length of 2.35 Angstrom to a Si-H BC -Si bond length of 3.18 Angstrom. [31] Pre-straining the lattice with radiation damage results in a smaller length change upon H incorporation, thereby reducing the strain energy barrier to this process. Indeed, previous research has shown that the presence of this strain reduces the barrier to place H and H-H between neighboring Si-Si atoms, which lie along the <111> direction.…”
Section: Influence Of Stress and Strain Field On H-platelet Formationmentioning
confidence: 99%
See 1 more Smart Citation